A study of patients` quality of life before and after resections of brain meningioma - V. Yu. Cherebillo; M. Yu. Kurnukhina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective was to analyze and evaluate patients` quality of life before and after resection of brain meningioma.Methods and materials. We performed study of 31 patients with brain meningioma. The diagnosis of the studied patients was based on clinical and laboratory data, data of radiation and instrumental methods of research. The analysis of patients` quality of life was carried out in the preoperative, early and late postoperative periods. The patient` age ranged from 37 to 65 years; the median age was 57 years. We chose a special questionnaire-EORTC QLQ-C30 to assess quality of life of the studied pre- and postoperative periods. The questionnaire has been tested in many international clinical studies.Results. In the early postoperative period, the severity of pain increased in the patients under study, nausea and vomiting, constipation occurred more often. However, patients assessed their General health in both early and late postoperative periods better than before the operation. In the late postoperative period, there was a positive dynamics in all scales of the questionnaire.Conclusion. On examination of various parameters of quality of life before and after surgery in patients with brain meningioma, it was found that surgical intervention led to an improvement in the quality of life of patients.